Characterization, Classification and Evaluation of Soils in Semi-arid Ecosystem of Karvetinagaram Mandal of Chittoor district, Andhra Pradesh - NAIDU, M V S; D Gurudev; D Vasu; G. Krishna Reddy; G.P. Leelavathy (Journal of the Indian Society of Soil Science, 2024)
Seven typical pedons representing major land forms namely plains and uplands originated from granite-gneiss parent material in semi-arid eco-system of Karvetinagaram mandal under varying land uses in Chittoor district of Andhra Pradesh were studied for their morphological characteristics, physical and chemical properties and soil genesis. These soils were slightly acidic to slightly alkaline (pH 6.38 to 7.85) in reaction, non-saline (0.04 to 0.52 dSm-1), shallow to very deep and had isohyperthermic temperature and ustic soil moisture regime. Texture, organic carbon (OC), cation exchange capacity (CEC) and base saturation of the soils were found to varied from sand to sandy clay loam, 0.11 to 0.63 per cent, 9.65 to 26.84 cmol (p+) kg-1 soil and 71.65 to 90.39 per cent, respectively. Soils were low in available N (28.00 to 78.40 mg kg-1), medium to high in available phosphorus (20.55 to 44.58 mg kg-1), low to high in available potassium (42.78 to 193.98 mg kg-1) and sufficient in available sulphur (14.29 to 63.20 mg kg-1). The DTPA- extractable Zn (0.49 to 1.74 mg kg-1) was deficient to sufficient, whereas DTPA- extractable Cu (0.54 to 2.09 mg kg-1), Mn (1.90 and 17.25 mg kg-1) and Fe (4.60 to 14.97 mg kg-1) were sufficient. The pedons 1, 5, and 7 were grouped under Entisols due to absence of sub-surface diagnostic horizon and was classified as Lithic Ustorthents( pedons 1 and 7) and Typic Ustifluvents ( pedon 5). Pedons 4 and 6 were grouped under Inceptisols due to presence of cambic (Bw) sub-surface diagnostic horizon and classified as Fluventic Haplustepts. Pedons 2 and 3 were grouped under Alfisols due to the presence of argillic (Bt) sub-surface diagnostic horizon and classified as Typic Haplustalfs. All soils of the study area fall in agricultural land under land capability sub-classes viz., IIIs, IVs and IVes. On the basis of major soil constraints and potentials, suitable land use plan for Karvetinagaram mandal was suggested.